Development of Cost Effective Nutritive Diet for Children using Linear Programming Problem - Kumar, Vijay; Bisht, Akshay; Rahul, Kumar (International Journal of Computer Sciences and Engineering, 2025)
In this paper authors presents a case based on utilisation of widely known, simple and yet interesting LPP technique for Diet problems i.e. focusing on to optimized product mix with minimum resources. It focuses on developing an innovative product for 12-16 years old children by mixing five different ingredients to formulate a single product that would serve them with the major nutrients needed per day. The objective of work is to minimize the cost of raw material subject to fulfilment of recommended dietary allowance (RDA) values of children. The formulated problem was analysed using LINDO software and gives an optimum solution to minimize the cost for developed product mix. The solution of formulated problem suggests the combination of five ingredients i.e. Milk (200g); Green Beans (200g); Peas (310g); White Rice (200g); Wheat Grains (504g) to achieve the optimum product mix with the minimum cost of INR 64.16 per day or serving.